Kaidah – Kaidah Ushuliyah Dalam Hadist Ekonomi - Riza Arizona; Moh Bahrudin; Syamsul Hilal (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
It cannot be denied that every Muslim believes in the oneness of Allah and the apostleship of the Prophet Muhammad. But we also need to realize that humans are not only required to believe in the Prophet, but are required to follow and imitate him. Thus, just believing is not enough. However, you need to realize that imitating the Prophet does not mean following exactly everything the Prophet did, and abandoning everything he did not do. There are at least three problems that will arise if the establishment of Islamic law ignores ushuliyah rules; ambiguity in the use of ushuliyah rules, errors in understanding texts in the Al-Qur'an and Hadith, and broad interpretations because they are not focused on one or several ushuliyah rules. This illustrates that the position of ushuliyah rules: al-am, al-khas, al-amru and an-nahyu is very important as a methodology for determining Islamic law. The aim of the research is to determine the ushuliyah al-am, al-khas, al-amru and an-nahyu approaches as methodologies, procedures and problems in determining Islamic law. This research is qualitative research in the form of literature with an Ushul Fiqh approach.